Portal entreparques (2020)
Urban renovation presents itself as a great exercise for us architects, it allows us to propose a plethora of different scenarios (where of course limitations exist) as well as opportunities to bring back life into a part of a city which has clearly lost it. It is always a big challenge, especially when said exercise is developed by various parties, being as it is a combination of multiple scales and an amalgamation of intentions and interests (some which align, some which do not). The thesis project developed in the section of architect Carlos Campuzano had the primary goal of realizing a project of such nature, but much more grounded. Said project was presented as a real life architectural commission. This presented itself for us, as future professionals, an exercise whose purpose was to mediate the academic freedom and the real-life challenges which many professionals deal with in a daily basis. The following document is a compilation of all the work prior to the development of the architectural concept and the final product, it hopes to showcase all the effort and dedication (both as a group and as individuals) which was dedicated to the final project of our academic life.